"سياسات حماية الطفولة في الجزائر الواقع والتحديات " - العوني, حكيمة (جامعة الوادي university el-oued)
"حاولنا من خلال هذه المذكرة معرفة مختلف الأليات و القواعد الحماية الخاصة بالأطفال سواء الأطفال الذين هم في حالة الخطر ، و الأطفال الجانحين التي تعرف بشكل شائع التدابير التي هي عبارة عن نظام و نهج تربوي اجتماعي ظهر في أواخر القرون الوسطى و الملاحظ ان هذا النظام لم يتم تعريفه بطريقة واضحة من طرف فقهاء و علماء القانون ، و اشتد الخلاف بينهم في تعريف الطفل ، أو الحدث ، أو القاصر كما اختلفوا في تحديد مراحل الطفولة و تمييزها من حيث التكليف و المسؤولية الجزائية الملاحظ هو اهتمام التشريعات الحديثة بفئة من الأطفال التي تكون في حالة خطر حيث سنت لها بعض أليات الحماية الاجتماعية ، و لكن هناك تضارب و اختلاف بين هذه التشريعات فيما يخص تحديد الحالات التي يكون فيها الطفل في حالة الخطر ، و كما هو ظاهر المشرع الجزائري لم يحدد بشكل صريح و واضح حالات الخطورة التي تدفع بالطفل لارتكاب الجريمة. أعطى قانون رقم ( 15-12 ) المتعلق بحماية الطفولة لقاضي الأحداث سلطات واسعة في تحديد آلية أو القاعدة المناسبة للطفل و التي تتماشى و سنه الزمني ، و تنفيذه لها يعتبر تطبيقا لسياسة جزائ"Through this memorandum, we tried to know the various mechanisms and rules for protection for children, both children who are in a state of danger, and delinquent children, which are commonly known measures that are a system and a socio-educational approach that appeared in the late Middle Ages and it is noticed that this system was not implemented Defining it in a clear manner on the part of jurists and legal scholars, and the dispute intensified between them in defining the child, juvenile, or minor, as they differed in defining the stages of childhood and distinguishing them in terms of assignment and criminal responsibility What is noticeable is the interest of modern legislation in a group of children who are in a state of danger, as some mechanisms of social protection have been enacted for them, but there is a conflict and difference between these legislations regarding defining cases in which the child is in a state of danger, and as it appears the Algerian legislator did not specify Clearly and clearly the dangerous situations that lead children to commit the crime. Law No. (12-15) related to child protection gave a juvenile judge wide powers in determining the appropriate mechanism or rule for the child that is in line with his age, and its implementation is considered an implementation of a contemporary penal policy. "
م.س.ع.20
Keywords: سياسات - حماية - الطفولة; Childhood- protection - policies